Risk factors for infectiousness of patients with tuberculosis: a systematic review and meta-analysis. Issue 3 (17th January 2018) - Melsew, Y.A.; Doan, T.N.; Gambhir, M.; Cheng, A.C.; McBryde, E.; Trauer, J.M.
Abstract: We performed a systematic review and meta-analyses of studies assessing tuberculosis (TB) patient-related risk factors for transmission of Mycobacterium tuberculosis infection. Meta-analyses were conducted for sputum smear-positivity, lung cavitation and HIV seropositivity of index patients with both crude and adjusted odds ratios (AORs) pooled using random effect models. Thirty-seven studies were included in the review. We found that demographic characteristics such as age and sex were not significant risk factors, while behaviours such as smoking and alcohol intake were associated with infectiousness although inconsistently. Treatment delay of >28 days was a significant predictor of greater infectiousness. Contacts of sputum smear-positive index patients were found to be more likely to be infected than contacts of sputum smear-negative patients, with a pooled AOR of 2.15 (95% confidence interval (CI) 1.47–3.17, I 2 = 38%). Similarly, contacts of patients with the cavitary disease were around twice as likely to be infected as contacts of patients without cavitation (pooled AOR 1.9, 95% CI 1.26–2.84, I 2 = 63%). In contrast, HIV seropositive patients were associated with few contact infections than HIV seronegative patients (AOR 0.45, 95% CI 0.26–0.80, I 2 = 52%). In conclusion, behavioural and clinical characteristics of TB patients can be used to identify highly infectious patients for targeted interventions.